Exact order of approximation of periodic functions by one nonclassical method of summation of Fourier series - Kotova, O. V.; Trigub, R. M. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
By using an exact estimate for approximation by known trigonometric polynomials, we strengthen a Jackson-type theorem.Moreover, we determine the exact order of approximation of some periodic functions by these polynomials. For this purpose, we introduce a special modulus of smoothness.